Anti-nociceptive and anti-inflammatory activities of Atalantia retusa Merr. - Raga, Dennis D. (Animo Repository, 2010)
Atalantia retusa is an endemic medicinal plant used in the Philippines. Hexane extract from leaves were orally administered on rats and mice and tested using rat paw edema, formalin and writhing assays. Increased pain tolerance was observed in animals administered with the median dose (1.43 mg/Kg BW) in both somatic (P<0.05) and visceral (P<0.01) models by 6.05% and 55.48% better compared to the positive control. The degree of swelling was also reduced by the administration of 1.43 mg/Kg BW at 0.5 to 3.0h after carrageenan injection suggesting a high impact analgesic and anti-inflammatory effects of A. retusa hexane extract. © 2010 Phcog.net.